Intake, digestibility, milk yield and composition, and ingestive behavior of cows supplemented with byproducts from biodiesel industry - Goncalves Lima, Marcus Vinicius; Vieira Pires, Aureliano Jose; Silva, Fabiano Ferreira da; Teixeira, Fabio Andrade; Silva Castro Nogueira, Bruna Rafaela de Carvalho; Rocha, Leone Campos [UNESP]; Silva, Gleidson Pereira da; Andrade, Weudes Rodrigues; Pinto de Carvalho, Gleidson Giordano (Springer, 2021)
This trial aimed to analyze the effects of including three byproducts from the biodiesel industry on the intake, digestibility, milk yield and composition, and feeding behavior of lactating cows. Eight crossbred Holstein-Zebu lactating cows with average body weight 525 +/- 18.5 kg and average milk yield of 8 +/- 1.45 kg day(-1) were assigned to four treatments (diets) in a double-Latin square design, as follows: a diet based on corn- and soybean meal-based concentrate and three diets with 20% inclusion of byproducts from the biodiesel industry (cottonseed cake, sunflower meal, and castor bean cake) on a total dry matter basis. The cows were housed in individual covered stalls with concrete floor equipped with individual concrete troughs for feeding and automatic drinkers, and fed diets containing 60% sugarcane and 40% concentrate. The inclusion of the byproducts in the diet changed the intake, digestibility of some nutritional components, milk yield and composition, and feeding behavior of lactating cows. The use of cottonseed cake and sunflower meal in the diet increased milk yield, and fat-corrected milk yield; while the use of castor bean cake reduced the intake, digestibility of dry matter and total digestible nutrients, milk yield, and fat-corrected milk yield. The inclusion of byproducts from the biodiesel industry in the diets did not change the fat, lactose, total solids, and solids-not-fat of milk. Therefore, the cottonseed cake and sunflower meal can be included at up to 20% of the total diet.
Keywords: Alternative feed; Feeding behavior; Milk yield; Protein sources